Lexicographical considerations from the Ricardo Palma's «ballots»: for a lexicography more inclusive and for greater lexical competence - Vega Cernuda, Miguel Ángel (2020)
Starting from the purpose that led Ricardo Palma to the Peninsula in 1891, the expansion of the lexicographical treasure of the Spanish language, we can see that his work, reflected in Papeletas lexicográficas, was not in vain, although, despite the enrichment that has taken place since then, there is still much to be done. The analysis of four Spanish-American texts allows us to identify a significant number of mottos that still do not appear in our lexicographies.